Stroke rehabilitation: principles of stroke - Teasell, Robert (Henry Stewart Talks, 2021)
Stroke rehabilitation, Stroke impact, Importance of rehabilitation, Standardization of key elements of stroke rehab care, Stroke rehab units, Intensity of therapy, Early rehab, Individualizing treatment, Biomarkers, Propositional recovery, Evidence-based algorithm, Importance of caregivers